Agricultural water use efficiency to adapt climate change in Indo-Gangetic plains of south-east Asia - KINGRA, P K; KAUR, RAMANJIT; MAJUMDER, DEBJYOTI; SINGH, SOM PAL; BUTTAR, G S (The Indian Journal of Agricultural Sciences, 2021)
Enhancing crop water productivity by genetic improvements or agronomic manipulations and reducing evapotranspiration losses from soil and plant surface is the need of the hour. Selection and breeding of traits which lead to increase in crop and water productivity like early maturing and stress tolerant cultivars with deep and thick root system, hairy leaves and increase in partitioning of assimilates towards grains etc. can help in increasing the water productivity. Different management options like, alteration in planting time, more water efficient planting methods, tillage practices, irrigation management, intercropping, use of anti-transpirants, row orientation, planting geometry and application of mulches and shelter belts can play important role for sustainability of water resources and crop productivity. However, the best option varies according to the location, prevailing weather conditions as well as social and economic conditions of the farmers.